2022
DOI: 10.1007/s00276-022-02974-z
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspective on the interactive online anatomy labs during the COVID-19 pandemic

Abstract: Purpose New training methods sprung up using communication technologies after the suspension imposed on Greek Universities due to restrictive measures against the COVID-19 pandemic. The current questionnaire-based study evaluates the efficacy and utility of the interactive online anatomy labs (ONALs) in assisting the assimilation of anatomy and substituting dissection labs during the pandemic. Methods ONALs consisting of video recorded demonstrations of dissected cadave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, there is now great concern about the safety and origin of the cadavers, their cause of death and whether they were infected by SARS-CoV-2 and whether this could represent a risk of infection for those who handle them. Regulations must be implemented to guarantee safety and teaching can resume as soon as possible as before, as well as being complemented by the technological tools available today [3,5].…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is now great concern about the safety and origin of the cadavers, their cause of death and whether they were infected by SARS-CoV-2 and whether this could represent a risk of infection for those who handle them. Regulations must be implemented to guarantee safety and teaching can resume as soon as possible as before, as well as being complemented by the technological tools available today [3,5].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Ioannis Antonopoulus et al 2022 [5] examined pre-recorded videos of the tutor performing cadaver dissection and interacting synchronously with the students through 3 different anatomical sections with different number of sessions including the possibility for the tutor to pause the video and answer students' questions as well as reaffirming critical points of the dissection and at the end asking questions to ensure understanding of the learning objectives of each session. The labs were well accepted by the students because of the interaction between student and tutor, however they agreed that face-to-face dissection will continue to be the mainstay of teaching.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surge of online anatomy content generation has prompted multiple studies on the effectiveness of this form of anatomy education from students' perspectives on their learning. These studies have yielded mixed results with regard to students' perceptions toward online education with some indicating favorable views based on the convenience of online learning, 2 accessibility of content, 3 and ideal conditions for self‐directed learning 4 ; while others indicating negative views related to the lack of personable interactions in an online curriculum, 5 inability to work with specimens 6 and encounters with technical difficulties 7 . One study used Q‐methodology (a semi‐quantitative qualitative approach) to explore undergraduate student perceptions toward an online curriculum of anatomy and physiology 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…A study investigating the quality of 235 surface anatomy teaching videos on YouTube concluded that 73% were not useful educationally [24]. Similarly, a recent study demonstrated that online anatomy practical demonstration could be a supplementary teaching method for better outcomes [25].…”
mentioning
confidence: 99%